Factors Determining Children's Private Health Insurance Enrolment and Healthcare Utilization Patterns: Evidence From the 2008 to 2011 Health Panel Data - Jawoon Shin; Tae-Jin Lee; Sung-il Cho; Seung Ah Choe (Korean Society for Preventive Medicine, 2015)
Objectives: Parental socioeconomic status (SES) exerts a substantial influence on children's health. The purpose of this study was to examine factors determining children's private health insurance (PHI) enrolment and children's healthcare utilization according to PHI coverage. Methods: Korea Health Panel data from 2011 (n=3085) was used to explore the factors determining PHI enrolment in children younger than 15 years of age. A logit model contained health status and SES variables for both children and parents. A fixed effects model identified factors influencing healthcare utilization in children aged 10 years or younger, using 2008 to 2011 panel data (n=9084). Results: The factors determining children's PHI enrolment included children's age and sex and parents' educational status, employment status, and household income quintile. PHI exerted a significant effect on outpatient cost, inpatient cost, and number of admissions. Number of outpatient visits and total length of stay were not affected by PHI status. The interaction between PHI and age group increased outpatient cost significantly. Conclusions: Children's PHI enrolment was influenced by parents' SES, while healthcare utilization was affected by health and disability status. Therefore, the results of this study suggest disparities in healthcare utilization according to PHI enrollment.